2022
DOI: 10.7759/cureus.31329
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Injury, Vitreous Hemorrhage, and Rhegmatogenous Retinal Detachment Following Long Needle Peribulbar Anesthesia: A Case Report and Article Review

Abstract: Rhegmatogenous retinal detachment (RRD) following retrobulbar or peribulbar anesthetic injection is a rare but serious complication that often results in poor visual outcomes. Thus, extreme caution should be exercised while administering local ocular anesthesia due to the potential complications arising from local orbital anesthesia. These complications may occur locally or systemically and may arise immediately or be delayed. This case report is on a female patient who sustained optic nerve injury and RRD due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Alrajhi et al [ 22 ] reported a case of globe penetration after a PBA for cataract surgery, and on the day after surgery, it showed VH and RD. Differently from our case, they reported no macular injury but found optic disk damage, probably due to the injection of the anesthetic inside the globe, with a final BCVA of light perception even after retinal reattachment.…”
Section: Discussionmentioning
confidence: 99%
“…Alrajhi et al [ 22 ] reported a case of globe penetration after a PBA for cataract surgery, and on the day after surgery, it showed VH and RD. Differently from our case, they reported no macular injury but found optic disk damage, probably due to the injection of the anesthetic inside the globe, with a final BCVA of light perception even after retinal reattachment.…”
Section: Discussionmentioning
confidence: 99%